Jepara, ukiran dan perubahan jaman - Bambang Kartono Kurniawan; Widyastuti Wiyoto (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2018)
Jepara is one of the cities ini Central Java which is famous for its carving furniture. People in this area known to have talent in the field of carving. Motifs and ornaments applied to Jepara carving furniture are influenced by various patterns and motifs from various regions from outside Jepara both regional and foreign countries that adapt to local culture. The development of Jepara carving furniture has always been related to human behavior and paradigms in order to create the value of culture itself. In every dynamic movement of Jepara society, the value of Jepara carving style proceeds to follow the change of time.Key words: Jepara, carving, change